Aktivitas Komunikasi Pemasaran Efektif Jasa Kurir Dan Logistik Pt Pos Indonesia Melalui Instagram @posaja.official - Syarifah, Fadia Anindita; Reza, Adrio Kusuma (eProceedings of Management, 2024)
Many companies are starting to innovate new technological transformation, which is digital marketing. One of thedigital marketing techniques that is commonly carried out by business actors is using Instagram as a social media.PT Pos Indonesia, is one of the state-owned companies that uses Instagram to follow the flow of new mediadevelopments with the @posaja.official account. The purpose of this study is to find out the marketing communicationstrategy carried out by PT Pos Indonesia in marketing its courier and logistics services through Instagram@posaja.official. This study uses a descriptive qualitative research method. The research data was taken through theobservation process, interviews with five informants, and literature studies. This research uses the theory of effectivemarketing communication strategies. The results of the study show that the messaging strategy used by PT PosIndonesia to market its courier and logistics services has been effective but has not met consumer needs for detailedinformation. PT Pos Indonesia uses both creative forms of emotional and rational messages in conveying itsinformation. In terms of media strategy, in this study, PT Pos Indonesia uses a direct communication channel, namelyInstagram, by utilizing some of its features, but there are still many features that can be improved. Consumer gapsthat are used are in the form of holiday celebrations, twin date events, and regional birthdays. Keywords-marketing communications, marketing communication strategies, Instagram.